2018
DOI: 10.1007/978-3-030-03402-3_28
|View full text |Cite
|
Sign up to set email alerts
|

How Much Is My Car Worth? A Methodology for Predicting Used Cars’ Prices Using Random Forest

Abstract: Cars are being sold more than ever. Developing countries adopt the lease culture instead of buying a new car due to affordability. Therefore, the rise of used cars sales is exponentially increasing. Car sellers sometimes take advantage of this scenario by listing unrealistic prices owing to the demand. Therefore, arises a need for a model that can assign a price for a vehicle by evaluating its features taking the prices of other cars into consideration. In this paper, we use supervised learning method namely R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 3 publications
1
11
0
3
Order By: Relevance
“…This model produces an accuracy of 0.977 or 97.7%. This value is excellent as the accuracy measurement carried out by previous studies, one of which is stated in research [23] which has an R2 score on data testing of 83.63%.…”
Section: Discussionsupporting
confidence: 55%
“…This model produces an accuracy of 0.977 or 97.7%. This value is excellent as the accuracy measurement carried out by previous studies, one of which is stated in research [23] which has an R2 score on data testing of 83.63%.…”
Section: Discussionsupporting
confidence: 55%
“…In the study, he used 252645 vehicle data and 139 variables and achieved a success rate of approximately 66% [28]. Pal et al (2018) used Random Forest, a controlled learning method to estimate the price of used cars. A Random Forest with 500 Decision Trees was created to train the data.…”
Section: Resultsmentioning
confidence: 99%
“…From the test results, it was found that the accuracy of the training was 95.82% and the test accuracy was 83.63%. The model was able to accurately estimate the price of the cars by choosing the most suitable features [17]. Noor and Jan (2017) offer a vehicle price forecasting system using the supervised machine learning technique in their articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the model proposed by Nabarun Pal et al [2], factors such as age of the car, its make, the origin of the car (original country of the manufacturer), its mileage (number of kilometers has run) and its horsepower were considered as the attributes. Fuel price is also given great importance.…”
Section: Related Workmentioning
confidence: 99%